MORPHOLOGICAL PREDICTORS OF KIDNEY ALLOGRAFT (KAG) FUNCTION DURING FIRST POSTTRANSPLANT YEAR - A. V. Trailin; T. N. Nikonenko; A. S. Nikonenko; T. I. Ostapenko; N. N. Polyakov; P. V. Pavlov; O. D. Pokrova (Вестник трансплантологии и искусственных органов, 2010)
The retrospective analysis of the influence of histological changes in donor kidneys on the KAG function during first year was conducted in 75 recipients of a cadaveric kidney. The state of tubuli, glomeruli, interstitium, vessels was assessed semiquantitatively in the material of «0»-biopsies. The endpoints were serum creatinine and glomerular filtration rate at 3, 6 and 12 months. KAG function in the first year is programmed by histological changes in all compartments of donor kidney. Influence of histological changes is time-dependent: the effect of ischemic damage shows up quickly, but disappeared after 6 months; the effect of arteriolohyalinosis and arteriosclerosis begins to show up later – since 6 months; changes in glomeruli have influence on a KAG function in 3 months and 1 year; interstitial fibrosis in cortex and medulla negatively influences KAG function on the extent of all first year. Our data argue for the necessity of «0»-biopsies examination for the prediction of KAG subsequent function.